THE PORTRAYAL OF FEMALE CONVICTS IN THE NEWS REPORTING OF CANING EXECUTION IN ACEH - Ainal Fitri; Febri Nurrahmi (al-Balagh : Jurnal Dakwah dan Komunikasi, 2021)
A prior observation indicated different portrayals of male and female convicts in caning execution news on five local online media in Aceh from 2018 until 2020. This study focuses on the emerging discourse surrounded female convicts. The study aims to discover the reality concerning context, production, text consumption, and social-cultural aspects influencing the discourse production within the text. This qualitative-descriptive study analyzed data from fifteen caning execution news, in-depth interviews with seven journalists, two editors, and one member of the Alliance of Independent Journalist Â Banda Aceh chapter (Aliansi Jurnalis Independen/AJI Banda Aceh). This study utilized Norman Faircloughâ€™s critical discourse analysis as the data analysis method. The findings revealed that the female convicts dominated news about caning, especially in khalwat and ikhtilat cases. Female convicts were represented as figures who violated social and moral norms, gender stereotypes, and expectations of femininity. This discourse benefited news organizations economically and also promoted discrimination against female convicts.